(3efgGL GdOcGf hOSJhQ GdCYjGf aj JQcjH GdCOhjI GdfGaYI ddEfSGfs - (3Gdchgjf GdYWGQ GdGSQGFjdj , OGhO Hf CHj fUQ Hf MaGX, CHh Gdefj,J (B608 (3g` s
(3ChdgG (B:s
(3GdHGH GdKGfi hGdYTQhf ai GdChRGf hGdecGjjd eQJHI Ydi MQha GdeYLe s
(3BNQgG (B:s
(3hGMVQGf GdHjY MGLI s
(3KdGK hQbGJ efg JTeds
(3GdHGH GdKGfi hGdYTQjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B143s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B189 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs